Is Recurrent Perseveration a Product of Deafferented Functional Systems with Otherwise Normal Post-Activation Decay Rates? - Buckingham, Hugh W; Buckingham, Sarah S (Clinical linguistics & phonetics, 2011)
Recent work in neuropsychology, clinical aphasiology and neuropharmacology have presented evidence that the causative substrates of recurrent perseveration in adults with aphasia are more recondite and subject to distinct interpretations than originally thought. This article will discuss and evaluate how various proposals from theory, from the clinic and from drug therapy interact and compete in the search for a cause or causes of recurrent perseveration.